PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA PADA MURID KELAS IV SDN 1 SUKAMULIA - Ratnasari, Meily; Kudsiah, Musabihatul; Atsarwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aimed to improve the learning outcomes of fourth-grade students in Pendidikan Pancasila through the implementation of the Problem Based Learning (PBL) model at SDN 1 Sukamulia. The research was motivated by the low learning outcomes of students, as indicated by the classical learning mastery in the pre-cycle which was only 44.44%. The research involved 27 students and was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. Data were collected through learning outcome tests and observations of teacher and student activities. The learning outcomes were analyzed using classical learning mastery and classical absorption, while teacher and student activities were analyzed descriptively based on the percentage of observation results. The results showed an improvement in learning outcomes following the implementation of PBL. The average score increased from 67.78 in the initial condition to 73.70 in Cycle I and 88.89 in Cycle II. Classical learning mastery increased from 44.44% to 70.37% and reached 92.59% in Cycle II. Teacher activity increased from 72.50% in Cycle I to 92.50% in Cycle II, while student activity increased from 60% to 90%. These findings indicate that the Problem Based Learning model can improve both the learning process and learning outcomes of fourth-grade students in Pendidikan Pancasila. The research was concluded in Cycle II because all predetermined success indicators had been achieved.